The Role Of Creativity Analysis And Design Thinking Process To Improve Product Innovation Sehatea - Putri, Julia (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2024)
The purpose of this study was to determine the effect of the role of creativity in thought process design on increasing Sehatea product innovation, as well as to find out the challenges that will be faced and how to handle them in increasing Sehatea product innovation. In this study, the type of data used by the author is associative data. In this study, data was obtained by distributing questionnaires to Sehatea consumers as many as 100 respondents regarding responses about the role of creativity analysis in the design thinking process to increase Sehatea product innovation. From the results of variable testing carried out between the role of creativity and innovation, it can be seen that the role of creativity has a positive and significant effect on Sehatea product innovation.